2015
DOI: 10.1007/s11266-015-9629-4
|View full text |Cite
|
Sign up to set email alerts
|

NPO Financial Statement Quality: An Empirical Analysis Based on Benford’s Law

Abstract: In order to assess the accuracy of the figures reported in NPOs' financial statements, I perform a digital analysis on Belgian non-profit organizations' financial statements for accounting years 2007 up to 2012. Specifically, I compare observed frequencies for digits in the second-from-the-left position with expected frequencies based on Benford's Law. Results based on the full sample indicate that observed frequencies strongly conform to Benford's Law (and thus suggest a high degree of accuracy of the figures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Dang and Owens (2019) do not only test organizational age but also find that larger British organizations have larger deviations. Van Caneghem’s (2016) analysis of Belgian nonprofits finds the opposite, using inferential statistics for the Benford distribution of the second digit. Using data on Ugandan nonprofits, Dang et al (2019) found a U-shaped relationship between organizational age and MAD, with young and old organizations less compliant than the middle-aged.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Dang and Owens (2019) do not only test organizational age but also find that larger British organizations have larger deviations. Van Caneghem’s (2016) analysis of Belgian nonprofits finds the opposite, using inferential statistics for the Benford distribution of the second digit. Using data on Ugandan nonprofits, Dang et al (2019) found a U-shaped relationship between organizational age and MAD, with young and old organizations less compliant than the middle-aged.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this article is the first academic study to apply Benford analysis to U.S. nonprofit data. We have located only two articles (Van Caneghem, 2016: Belgian nonprofit organizations; Dang, Burger, & Owens, 2019: Ugandan non-governmental organizations [NGOs]) and one working paper (Dang & Owens, 2019: UK charities) that applied Benford analysis to nonprofit financial data in other countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonprofits typically rely upon volunteers to fill relevant financial accountability roles in the organization (Jang, Wang, and Yoshioka 2016), including the role of treasurer. A significant body of literature has pointed to this factor as a potential cause of inaccuracies in nonprofit financial records (see Frumkin and Kim 2001;Trussel 2003;van Caneghem 2016). It is also possible that such misrepresentations may result from intentional accounting manipulation.…”
Section: Incentives For Accounting Manipulationmentioning
confidence: 99%